1985
DOI: 10.1002/jca.2920020304
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐flow techniques for platelet concentrate collection: A step toward standardization and yield predictability

Abstract: This study chronicles leukocyte- and erythrocyte-depleted platelet concentrate collection by a dual stage channel in which three variables: 1) donor peripheral blood platelet concentration, 2) total blood processed, and 3) collection volume were statistically correlated with platelet yield as determined by a multiple regression analysis of single variables. Platelet concentration in the final yield was related to donor precount and collection rate, and could be varied as indicated for individual applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…While the focus of their paper was directed toward lymphocyte contamination of the platelet concentrates, the calculation results from reported preprocedure platelet counts (250 k 90 x lO'/liter), the number of cycles performed (usually seven or eight), and the formula provided to compute the total blood processed, suggest that, with the surge method, 36% of circulating platelets were removed during harvesting and 44 % when the red cell methods were employed. Ogata et al [8] also reported that yield in the Haemonetics is related to preprocedure platelet count and the "blood drawing time," which is an indirect reflection of the total blood processed. Standardizing data collection for platelet collection procedures from all methods of preparation of platelet concentrates might offer the means by which instrument and procedure modifications could be accomplished to improve platelet yields.…”
Section: Discussionmentioning
confidence: 99%
“…While the focus of their paper was directed toward lymphocyte contamination of the platelet concentrates, the calculation results from reported preprocedure platelet counts (250 k 90 x lO'/liter), the number of cycles performed (usually seven or eight), and the formula provided to compute the total blood processed, suggest that, with the surge method, 36% of circulating platelets were removed during harvesting and 44 % when the red cell methods were employed. Ogata et al [8] also reported that yield in the Haemonetics is related to preprocedure platelet count and the "blood drawing time," which is an indirect reflection of the total blood processed. Standardizing data collection for platelet collection procedures from all methods of preparation of platelet concentrates might offer the means by which instrument and procedure modifications could be accomplished to improve platelet yields.…”
Section: Discussionmentioning
confidence: 99%
“…Since the development of plasmapheresis technology and transfusion medicine in the 1950s [6,7], spontaneous hemorrhage as a primary cause of mortality from treatment-related myelosuppression has decreased, and infectious complications remain the leading cause of morbidity and mortality in children and adults with acute leukemia [8][9][10]. The degree and duration of neutropenia are predictive, with high-risk patients considered to be those with prolonged (>7 days duration) and profound (absolute neutrophil count (ANC) <100 cells/mm 3 ) neutropenia [11].…”
Section: Introductionmentioning
confidence: 99%